A clown, a political messiah or a punching bag? Rethinking the performative identity construction of celebrity through social media. Issue 3 (September 2018) - Tse, Tommy; Leung, Vivienne; Cheng, Kimmy; Chan, Joey
In meeting the changing demands of authenticity and visibility in social media, performances of identity and connections are discussed to entail new sociotechnical labours and digital literacies. Research has looked into the construction and presentation of celebrity identities, in light of these developments, but has paid little attention on the celebrities' experiences and perspectives, which is also due to the lack of willingness of industry insiders in this culturally sensitive business to be interviewed and genuinely talk about its problems. Twelve in-depth interviews with celebrities and entertainment industry practitioners were conducted between 2014 and 2015. Particularly, this article draws on the cases of two established celebrities in Hong Kong and China, and assesses how and why they were unable to actively construct and perform their preferred media identities, highlighting the blurring boundaries among traditional celebrities, micro-celebrities and ordinary people for their construction of online identities through social media, and also elucidating the opportunities and challenges posed by today's evolving media environment. We argue that social media only superficially open up a site of counter-narratives for celebrities to resist the identities imposed on them by the mainstream media and online audiences. The interviewed celebrities' contradictory experiences in their self-presentations in social media offer alternative angles to understanding the incoherent and unstable celebrity identity production processes, the blurring boundaries between celebrities and ordinary people through such processes as well as the celebrities' capacity to reclaim control in asserting their 'true' selves.